2010
DOI: 10.3758/brm.42.1.82
|View full text |Cite
|
Sign up to set email alerts
|

Norms for two types of manipulability (graspability and functional usage), familiarity, and age of acquisition for 320 photographs of objects

Abstract: There is increasing interest in the role that manipulability plays in processing objects. To date, Magnié, Besson, Poncet, and Dolisi's (2003) manipulability ratings, based on the degree to which objects can be uniquely pantomimed, have been the reference point for many studies. However, these ratings do not fully capture some relevant dimensions of manipulability, including whether an object is graspable and the extent to which functional motor associations above and beyond graspability are present. To addr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
46
1
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 23 publications
1
46
1
3
Order By: Relevance
“…In addition, AoA contributes to performance on tasks that differ between young and older adults, such as lexical decision and semantic categorization (De Deyne & Storms, 2007). Therefore, although AoA effects have been studied with different age groups, most of the existing AoA norms in different languages have come from student/young adult samples (e.g., Carroll & White, 1973a;Marques, Fonseca, Morais, & Pinto, 2007;Salmon, McMullen, & Filliter, 2010). Even when the samples have large age ranges (e.g., 18 to 50 years in Carroll & White, 1973a, or 19-56 in Tsaparina, Bonin, & Méot, 2011), it has not been possible to report and compare the AoAs for different age groups due to the small numbers of participants in different age groups.…”
Section: The Present Studymentioning
confidence: 99%
“…In addition, AoA contributes to performance on tasks that differ between young and older adults, such as lexical decision and semantic categorization (De Deyne & Storms, 2007). Therefore, although AoA effects have been studied with different age groups, most of the existing AoA norms in different languages have come from student/young adult samples (e.g., Carroll & White, 1973a;Marques, Fonseca, Morais, & Pinto, 2007;Salmon, McMullen, & Filliter, 2010). Even when the samples have large age ranges (e.g., 18 to 50 years in Carroll & White, 1973a, or 19-56 in Tsaparina, Bonin, & Méot, 2011), it has not been possible to report and compare the AoAs for different age groups due to the small numbers of participants in different age groups.…”
Section: The Present Studymentioning
confidence: 99%
“…These scales were mostly used as variants of Likert-type scales (see the descriptions in Table 3) in studies in which norms for other psycholinguistic variables, such as familiarity, imageability, concreteness, meaningfulness, visual complexity, name and image agreement, and subjective frequency were collected in addition to AoA (e.g., Akinina et al, 2014;Alario & Ferrand, 1999;Bakhtiar, Nilipour, & Weekes, 2013;Barca, Burani, & Arduino, 2002;Bird, Franklin, & Howard, 2001;Bonin, Peereman, Malardier, Méot, & Chalard, 2003;Cuetos, Ellis, & Alvarez, 1999;Della Rosa, Catricalà, Vigliocco, & Cappa, 2010;Dimitropoulou, Duñabeitia, Blitsas, & Carreiras, 2009;Ferrand et al, 2008;Gilhooly & Logie, 1980;Liu, Hao, Li, & Shu, 2011;Liu, Shu, & Li, 2007;Manoiloff, Artstein, Canavoso, Fernández, & Segui, 2010;Moreno-Martínez, Montoro, & Rodríguez-Rojo, 2014;Nishimoto, Miyawaki, Ueda, Une, & Takahashi, 2005;Pind, Jónsdóttir, Gissurardóttir, & Jónsson, 2000;Raman, Raman, & Mertan, 2014;Salmon, McMullen, & Filliter, 2010;Shao, Roelofs, & Meyer, 2014;Sirois et al, 2006;Snodgrass & Yuditsky, 1996;Stration, Jacobus, & Brinley, 1975;Tsaparina, Bonin, & Méot, 2011;Vinson, Cormier, Denmark, Schembri, & Vigliocco, 2008). Other scales have sometimes been modified according Table 3 Most popular scales used in the studies on subjective age of acquisition Scale Description Examples of Studies 5-point 1 = 3 years or earlier, 2 = 4 to 6 years, 3 = 7 to 9 years, 4 = 10 to 12 years, 5 = 13 years or later Akinina et al (2014); …”
Section: Methodological Aspects Of Aoa Studiesmentioning
confidence: 99%
“…Hirsh and Funnell (1995) found that familiarity predicted the performance of patients suffering from progressive semantic dementia, as well as that of aphasics (Feyereisen, Van der Borght, & Seron, 1988). As in most normative studies, pictures of objects were presented, and the conceptual familiarity scores collected (e.g., Alario & Ferrand, 1999;Manoiloff, Artstein, Canavoso, Fernández, & Segui, 2010;Morrison, Chappell, & Ellis 1997;Rossion & Pourtois, 2004;Salmon et al, 2010;Sanfeliù & Fernandez, 1996;Snodgrass & Vanderwart, 1980). These measures could, in principle, be obtained from the modal names, since in certain studies conceptual familiarity scores have been used to investigate the involvement of semantic codes in visual word recognition (e.g., Bonin, Barry, Méot, & Chalard, 2004).…”
Section: The Russian Languagementioning
confidence: 99%
“…Peereman, Malardier, Méot, & Chalard, 2003, for a set of 299 objects in French; Brodeur, Dionne-Dostie, Montreuil, & Lepage, 2010, for a set of 480 photographs of objects in English; Himmanen, Genteles, & Sailor, 2003, for 60 line drawings that make up the Boston Naming Test; Martein, 1995, for a set of 216 objects in Dutch; Salmon, McMullen, & Filliter, 2010, for a set of 320 black-and-white photographs of objects). Despite the large number of normative studies conducted using the Snodgrass and Vanderwart pictures, it is still important to collect additional languagespecific norms (Sanfeliù & Fernandez, 1996), because norms collected in one language may not be suitable for use in another.…”
mentioning
confidence: 99%